Investigation of the development and evolution of the mammalian cerebrum using gyrencephalic ferrets - Masanori Imamura; Mayuko Yoshino; Hiroshi Kawasaki (European Journal of Cell Biology)
Mammalian brains have evolved a neocortex, which has diverged in size and morphology in different species over the course of evolution. In some mammals, a substantial increase in the number of neurons and glial cells resulted in the expansion and folding of the cerebrum, and it is believed that these evolutionary changes contributed to the acquisition of higher cognitive abilities in mammals. However, their underlying molecular and cellular mechanisms remain insufficiently elucidated. A major difficulty in addressing these mechanisms stemmed from the lack of appropriate animal models, as conventional experimental animals such as mice and rats have small brains without structurally obvious folds. Therefore, researchers including us have focused on using ferrets instead of mice and rats. Ferrets are domesticated carnivorous mammals with a gyrencephalic cerebrum, and, notably, they are amenable to genetic manipulations including in utero electroporation to knock out genes in the cerebrum. In this review, we highlight recent research into the mechanisms underlying the development and evolution of cortical folds using ferrets.